Novices Assigned Nutraceuticals: Matching Subject Strengths Uncovered by Same-Day, Simple-Strategy Searches across EBSCO Versions of Four Major Databases to Different Undergraduate Science Majors. Issue 1 (2nd January 2017) - Stankus, Tony
ABSTRACT: An undergraduate assignment on the topic of nutraceuticals is proposed with goals that include familiarization of students with more-focused, subject-specific databases. Four searches, conducted on the same day using the same simple search strategy, on four likely EBSCO-version databases uncovered differing degrees of coverage of key journals. Unsurprisingly, MEDLINE reported the most papers from the journals of the mainstream clinical nutrition community. Agricola provided the most in-depth coverage of key journals in the chemical analysis of foodstuffs, including nutraceuticals. CABI provided the most references overall by far and led in coverage of many horticultural, general food science, and technology journals, as well as those narrowly focused on nutraceuticals, functional foods, and bioactive botanicals. Despite having comparatively fewer references overall, FSTA showed an ability to single out papers on promising new technologies in nutraceutical processing.